Aktivitas-Aktivitas & Penyelesaian Konflik Internal Kekaryawanan - Nurhayani Nurhayani; Kezya Meylani Fernanda Putri; Lidiya Rima Ranti; Yusawinur Barella (Lembaga Pengembangan Kinerja Dosen, 2024)
In a company there are employee activities which include promotion, demotion and dismissal and retirement. During employee activities, it does not rule out the possibility of conflicts, both personal, intragroup, and intergroup. Every conflict must have a resolution. Some ways of resolving internal employee conflicts include open and transparent communication, mediation, individual counseling, training and education. In writing this journal, the method used is a library research method, by taking data or information from various sources such as books, notes, and research reports. The purpose of writing this journal is to provide readers with an understanding of internal employee activities, employee conflicts and their resolution. The results of this study are a discussion that we have compiled in this journal.